Desain Didaktis Konsep Reaksi Reduksi Oksidasi - Rizky Brehnaputrifajar Khaerudin; Asep Supriatna; Sumar Hendayana; Herwantono Herwantono (Orbital: Jurnal Pendidikan Kimia, 2023)
The lack of didactic anticipation as reflected in lesson plans can have an impact on the less optimal learning process for each student so that learning obstacles arise. One effort to overcome this is to design learning through didactic design. This study aims to develop a didactic design in reducing learning obstacles in the concept of redox reactions. The method used in this research is a qualitative research method. The research design used is Didactical Design Research (DDR). Data collection techniques used are tests, observations, interviews and documentation. Respondents in this study were 30 students of the UPI Pilot Laboratory High School in class XI IPA 2 and 28 students in class X. Based on the results of the study, it was found that the didactic design developed in the form of Chapter Design and Lesson Design included providing an understanding of concepts through the provision of phenomena followed by experiments or demonstrations in general, which ran smoothly. The existence of Chapter Design and Lesson Design components aims to make students obtain the material. The other goal is to make it easier for teachers to achieve better educational goals by bringing out predictions of student responses and prepared teacher anticipation. This didactical design can reduce learning barriers and can improve students' abilities. It can be concluded that the didactic design of the concept of oxidation-reduction reactions is effective as an alternative teaching material used in the learning process.